Total anomalous connection of pulmonary veins to the portal vein. Value of multislice angiotomography. Report on three cases - Sara Alejandra Solórzano-Morales; Francisco Javier López-Elías; Javier Horacio López-Terrazas; Max Alberto Bernal-Moreno; Alexis Javier Palacios-; Alfredo Bobadilla-Aguirre (Instituto Nacional de Pediatría, 2014)
Objective: Present tomographic data from the patients with emphasis on structural characteristics. Material and method: Retrospective study of three patients in whom the four pulmonary veins connected to the portal vein. This malformation is one of the varieties of total anomalous connection of pulmonary veins. In any of them, the pulmonary veins do not connect to the left atrium and blood from the lung reaches the right atrium directly or through its tributary systems. In such cases, arterialized pulmonary blood and systemic venous blood mix at the site of the anomalous connection and a short circuit is formed from the right atrium to the left atrium through an interauricular communication, allowing patients to survive. Total anomalous connection of pulmonary veins accounts for between 0.4 and 2.0% of congenital heart diseases: it occurs in 6.8 of every 100,000 individuals. It is diagnosed in 68% of patients in neonatal stage, which reflects the severity of the condition. The infracardiac variety of total anomalous connection of pulmonary veins accounts for between 15 and 26% if all its varieties. Multislice angiotomography allows us to view the blood vessels and adjacent organs under consideration and obtain high-definition anatomic information. In the patients in this study, total anomalous connection of pulmonary veins to the portal vein was viewed with three-dimensional volumetric tomographic reconstructions and their correlation with ultrasonography studies.